Hypervalent aryliodine compounds as precursors for radiofluorination - Pike, Victor W. (Journal of labelled compounds & radiopharmaceuticals, 2018)
Over the last 2 decades or so, hypervalent iodine compounds, such as diaryliodonium salts and aryliodonium ylides, have emerged as useful precursors for labeling homoarenes and heteroarenes with no‐carrier‐added cyclotron‐produced [18F]fluoride ion (t1/2 = 109.8 min). They permit rapid and effective radiofluorination at electron‐rich as well as electron‐deficient aryl rings, and often with unrestricted choice of ring position. Consequently, hypervalent aryliodine compounds have found special utility as precursors to various small‐molecule 18F‐labeling synthons and to many radiotracers for biomedical imaging with positron emission tomography. This review summarizes this advance in radiofluorination chemistry, with emphasis on precursor synthesis, radiofluorination mechanism, method scope, and method application. Hypervalent iodine compounds, such as diaryliodonium salts and aryliodonium ylides, have emerged as useful precursors for labeling arenes, either as labeling synthons or as PET radiotracers, with no‐carrier‐added [18F]fluoride ion (t1/2 = 109.8 minutes). This review summarizes this advance in radiofluorination chemistry, with emphasis on precursor synthesis, radiofluorination mechanism, method scope, and method application.